Analisis Efektivitas Sistem Informasi Akuntansi Penerimaan Kas pada CV Bina Puskud Mandiri - Arfi, Muhammad; Agustiawan (JURNAL AKUNTANSI DAN MANAJEMEN, 2024)
The aim of this research is to determine the effectiveness of the implementation of the cash receipts accounting information system at CV Bina Puskud Mandiri, whether it is in accordance with applicable accounting standards in Indonesia and whether cash receipts are carried out manually or systemically. This research uses a qualitative descriptive type with data used as primary data and secondary data collected using interview methods, observation, documentation and the results of previous research. This research uses descriptive analysis techniques in data analysis techniques by analyzing information from sources through interviews. The research results show that the analysis of the cash receipts accounting information system was carried out manually using Microsoft Excel and cash receipts, recording and reporting were in accordance with the accounting standards applicable in Indonesia. Researchers have limited time in research which can have an impact on research results that are less comprehensive and obtain limited information.